A study on the dynamics and control of the soybean aphid - Peixoto, Magda S.; Barros, Laecio C.; Bassanezi, Rodney C.; Fernandes, Odair A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This paper uses a methodology based in Fuzzy Sets Theory in order to describe the interaction between the prey, Aphis glycines (Hemiptera: Aphididae) - the soybean aphid, and its predator, Orius insidiosus (Hemiptera: Anthocoridae) and to propose a biological control and a chemical control for soybean aphid. Economic thresholds were already developed for this pest. The model includes biotic (predator) and abiotic (temperature) factors, which affect the soybean aphid population dynamics.
Keywords: Fuzzy systems; Input variables; Mathematical model; Predator prey systems; Sociology; Statistics